Decision-Making Competence and Critical Thinking Ability among Triage Nurses in a Selected Hospital in Batangas, Philippines - Comia, Rejie Lunar; Floranda, Lualhati Maxima M.; Durante, Cherry Ann Garcia (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
Overcrowding and long waiting times remain perennial issues in many emergency departments globally, resulting in unsafe and inefficient care. To facilitate the treatment of patients that arrive in the Emergency Department a triage process is often implemented. Triage enables the Emergency Department staff to prioritize patient care so that patients requiring more immediate care are seen first. This study described the competence and critical thinking ability of triage nurses in a selected hospital in Lipa City, Batangas, Philippines. The quantitative descriptive correlational research design was used in this study. Data was gathered through a self-administered questionnaire that adopted Yoon Critical Thinking Disposition and Triage Decision Making Inventory by Cone (2000). Results showed that decision-making competency is significantly different among different age groups (F=40.93, p<0.0001). Respondents’ critical thinking ability based on objectivity, healthy scepticism, systematicity and intellectual fairness, intellectual curiosity, self-confidence and prudence was at moderate level, with composite means of 3.23, 3.43, 3.22, 3.37, 3.33, 3.28, and 3.27, respectively. Based on the results of the study, participants had a moderate level of critical thinking ability while doing triage. Also, over-all decision-making ability significantly increased with age and years of experience. Furthermore, objectivity, self-confidence, prudence and over-all critical thinking ability are significantly associated with age. Moreover, the triage nurses’ decision-making skills can be greatly influenced by their critical thinking ability.